Analisis Kebutuhan Pegawai Berdasarkan Latar Belakang Pendidikan Di Sekretariat Daerah Kabupaten Ogan Ilir - Inessia Inessia; Mody Sertian Amanda; Terttiaavini Terttiaavini (Jurnal Nasional Komputasi dan Teknologi Informasi (JNKTI), 2023)
Abstract - This study is entitled "Employee Needs Analysis Based on Educational Background at the Regional Secretariat of Ogan Ilir Regency". The purpose of this study was to analyze the number of employee needs based on educational background at the Regional Secretariat of Ogan Ilir Regency. This type of research uses a descriptive method with a qualitative approach. Data collection techniques used in this study were observation, interviews, documentation studies, and triangulation. The results of the study show that the job descriptions of each section at the Regional Secretariat of Ogan Ilir Regency are clear and listed in the job analysis document. Based on the analysis of employee needs, positions that experience a staff shortage include the works of technical policy reviewers and data and information processors. Judging from the comparison of needs and equipment, the number of staff shortages for these positions is 100 people, with details of the positions of technical reviewers of policies of 50 and data and information processors of 50 people. Therefore, it is better to add employees as needed based on relevant educational backgrounds as one of the job requirements.Keywords: Job Description, Employee Needs Analysis, Educational Background.